2018
DOI: 10.21686/1818-4243-2018-3-61-73
|View full text |Cite
|
Sign up to set email alerts
|

Modern digital educational tools and digital competence: analysis of cases and trends

Abstract: Ключевые слова: e-learning, инновации, LMS, цифровое образо-вание, Образование 3:0, MOOC, цифровые компетенции The introduction of digital tools takes place in all spheres of life, including the education. The author of this paper attempted to structure and characterize the existing digital educational tools in terms of functions and capabilities for users, characteristics of user interactions in tools. In the literary review in first part of this work, the current state of digitalization of various spheres of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…It should be noted that the first in their pedagogical practice, the elements of gamification are used by teachers of informatics. The main reason for this is the problem that teachers of other specialties lack the necessary competencies and technologies for the creation and implementation of game elements [9]. Based on this, it is necessary to borrow this effective method as soon as possible for the teaching staff of other disciplines, and for this, in turn, it is necessary to form the appropriate technological competencies from teachers of other sciences.…”
Section: Fig 2 Structure Of Distance Coursementioning
confidence: 99%
“…It should be noted that the first in their pedagogical practice, the elements of gamification are used by teachers of informatics. The main reason for this is the problem that teachers of other specialties lack the necessary competencies and technologies for the creation and implementation of game elements [9]. Based on this, it is necessary to borrow this effective method as soon as possible for the teaching staff of other disciplines, and for this, in turn, it is necessary to form the appropriate technological competencies from teachers of other sciences.…”
Section: Fig 2 Structure Of Distance Coursementioning
confidence: 99%
“…Perhaps, concerning this, teachers’ skills play a vital role in making the work meaningful for students. In explaining this notion, the study indicates that improved performance requires teachers to expand their professional competencies, substantially helping the students achieve their learning goals ( Kalimullina and Trotsenko, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…attitudes of children and their parents to various forms of learning in the digital educational space. Analysis of the scientific literature on the research problem (Ignatova, 2017;Kalimullina & Trocenko, 2018) has shown that currently there is practically no information which could be used to predict the risks of digitization in the educational sphere. Most of the work comes down to the description of problems, ascertains their presence, gives an assessment, but does not consider the problem in development.…”
Section: Fig 1 Percentage Of Children Living In the City And In Thementioning
confidence: 99%